2018
DOI: 10.1016/j.molcel.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Galectins Control mTOR in Response to Endomembrane Damage

Abstract: The Ser/Thr protein kinase mTOR controls metabolic pathways, including the catabolic process of autophagy. Autophagy plays additional, catabolism-independent roles in homeostasis of cytoplasmic endomembranes and whole organelles. How signals from endomembrane damage are transmitted to mTOR to orchestrate autophagic responses is not known. Here we show that mTOR is inhibited by lysosomal damage. Lysosomal damage, recognized by galectins, leads to association of galectin-8 (Gal8) with the mTOR apparatus on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
223
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(261 citation statements)
references
References 57 publications
24
223
2
1
Order By: Relevance
“…We found that during lysosomal damage MTOR is inactivated and that it translocates from the lysosomal membrane to the cytosol, similar to what happens during starvation [1]. Cytosolic lectins termed galectins, recognize membrane damage by binding to lumenal glycans upon their exposure to the cytosol as a consequence of endomembrane damage.…”
supporting
confidence: 61%
“…We found that during lysosomal damage MTOR is inactivated and that it translocates from the lysosomal membrane to the cytosol, similar to what happens during starvation [1]. Cytosolic lectins termed galectins, recognize membrane damage by binding to lumenal glycans upon their exposure to the cytosol as a consequence of endomembrane damage.…”
supporting
confidence: 61%
“…As a member of lectin family, LGALS8 (galectin‐8) plays key roles in various cellular processes, such as autophagy, cytoskeletal rearrangement, immunity and inflammation, as well as tumour progression . LGALS8 can recognize lysosome damage and promote autophagy through inhibiting mTOR activity . Remarkably, LGALS8 may serve as prognostic biomarkers in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis strains deficient in ESX-1 or PDIM synthesis show reduced galectin-3 or galectin-8 recruitment to intracellular sites of infection[23,24,33,34]. If the endosomal membrane is damaged, cytosolic galectins bind to lumenal β-galactoside-containing glycans that become exposed on damaged vesicles, and can be visualized by immunofluorescence microscopy[23,24,3336]. Differing from the role of ESX-1 in phagosomal permeabilization during M. tuberculosis and M. marinum infection, the involvement of M. marinum PDIM in this process has not been demonstrated.…”
Section: Resultsmentioning
confidence: 99%